The Existence of Customary Role In The Settlement of Marriage Disputes (A Study of The Role of Mamak Limo Suku In Jorong Sungai Sanda) - Fauzi, Fauzi; Eva, Yusnita (Jurnal Kajian dan Pengembangan Umat, 2025)
This research aims to understand the existence of customary systems in responding to marital disputes that occur in society. In the Minangkabau community, customs are inseparable from daily life. One such place is Jorong Sungai Sanda, where the presence of customs is still very strong. In Sorong Sungai Sanda, the term  mamak limo  is known, which refers to the head of customs. Whenever issues arise in the community, they report them to the  mamak  as the elder in society. This research is a field study. Data was obtained through interviews with relevant parties such as the mamak, the community, and other related parties.The conclusion of this research is that the role of  mamak  in the Jorong Sungai Sanda community is still very strong. In resolving marital disputes, the  mamak  plays an active role; when conflicts arise, it is the  mamak  who mediates to find a solution. The advantage of resolving disputes through this system is that it allows for quick resolution and avoids the emergence of new problems. However, in this dispute resolution, the  mamak  does not instruct their nephews to handle their divorces in court, which may lead to new issues in the future.